2017
DOI: 10.1097/wnr.0000000000000909
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal expression of thalamic GABAA receptor subunits in the stargazer mouse model of absence epilepsy

Abstract: Absence seizures are known to originate from disruptions within the corticothalamocortical network; however, the precise underlying cellular and molecular mechanisms that induce hypersynchronicity and hyperexcitability are debated and likely to be complex and multifactorial. Recent studies implicate impaired thalamic GABAergic inhibition as a common feature in multiple animal models of absence epilepsy, including the well-established stargazer mouse model. Recently, we demonstrated region-specific increases in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…GABA A R are pentameric ligand-gated ionotropic chloride (Cl − ) channels that are ubiquitously expressed in the central nervous system. They mediate the majority of fast inhibitory neurotransmission, play a fundamental role in restraining and sculpting neuronal activity, and have been implicated in animal models of seizures 25 , 26 . There are 19 GABA A R subunits (α1–6, β1–3, γ1–3, δ, ε, θ, π, and ρ1–3) with the most prevalent synaptic isoform comprising two α1, two β2, and one γ2 subunit 27 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…GABA A R are pentameric ligand-gated ionotropic chloride (Cl − ) channels that are ubiquitously expressed in the central nervous system. They mediate the majority of fast inhibitory neurotransmission, play a fundamental role in restraining and sculpting neuronal activity, and have been implicated in animal models of seizures 25 , 26 . There are 19 GABA A R subunits (α1–6, β1–3, γ1–3, δ, ε, θ, π, and ρ1–3) with the most prevalent synaptic isoform comprising two α1, two β2, and one γ2 subunit 27 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal tonic inhibition in the stargazer VP thalamic nucleus has previously been reported [ 34 ]. Moreover, we also reported an increase in tonic GABA A R subunits α4 and δ levels in the VP thalamic nucleus, but only after the onset of seizures in the stargazers [ 28 , 30 ]. To assess whether any changes in tonic GABA A R subunits occur in the adult stargazer primary SoCx, we conducted further semiquantitative WB analyses to investigate levels of GABA A R α4, α5, and δ subunits.…”
Section: Resultsmentioning
confidence: 99%
“…In the stargazer ventroposterior (VP) thalamic nucleus, we previously reported a specific increase in both tonic and phasic GABA A R subunits [ 28 , 29 ]. However, unlike the AMPA receptor loss, which is pre-seizure, the increase in GABA A R subunits expression in the thalamus occurs after the onset of seizures [ 30 ], and thus is unlikely to be causative of seizures, although a role in seizure maintenance should not be ruled out. GABA A Rs generate either phasic or tonic post-inhibitory currents depending on synaptic or extra-synaptic GABAergic activation, respectively [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research using the stargazer mouse model of absence epilepsy ( Barad et al, 2012 , 2017 ; Seo and Leitch, 2014 , 2015 , 2017 ; Adotevi and Leitch, 2016 , 2017 , 2019 ) has demonstrated that region-specific alterations in AMPA receptor expression in inhibitory microcircuits within the CTC network may be a key factor contributing to pathological hypersynchronous oscillatory activity in some forms of absence epilepsy. Specifically, a selective decrease in AMPA receptor expression at excitatory input synapses on RTN inhibitory interneurons from CT afferent projections (CT-RTN) but not at excitatory input synapses onto VP relay neurons (CT-VP) has been identified by Barad et al (2012) .…”
Section: Introductionmentioning
confidence: 99%